A data set of spectral volume light absorption by Gelbstoff (chromophoric dissolved organic matter, CDOM) from the German Bight, the River Elbe and the Southern North Sea (1954 - 2007) - Rüdiger Röttgers; Kerstin Heymann (PANGAEA, 2024)
A regional data set of the light volume absorption coefficient of Gelbstoff (also called chromophoric dissolved organic matter, CDOM) is presented. The data provided are results of laboratory analysis of samples taken at sea in the German Bight and the Southern North Sea as well as in the River Elbe, during the years 1992 to 2007. In addition, Gelbstoff data from Kalle (1956) and Doerffer (1979) of the same region are included after being transferred to the unit of absorption coefficient and corrected for scattering artifacts.